Successful recovery of a young man with traumatic brainstem ischemia in a motor vehicle accident - Dražen Radanović; Kristina Peić; Dušan Elboursh; Đurđina Bogosavljević; Jovana Antonijević; Uroš Mirčić; Bojan Čukić; Srbislav Pajić (Romanian Neurosurgery, 2023)
Introduction: The most common etiological factors of brainstem stroke and ischemia are atherosclerosis, thromboembolism, tumours, arterial dissection, and trauma. Infarction of the medulla oblongata in 73% of cases occurs as a result of stenosis of the vertebral arteries, 26% due to arterial dissection, while the topic of traumatic brainstem ischemia is still under-researched and under-represented.